Healthy lifestyle module for improving the quality of life of chronic kidney disease patients - Idar Sri Afriyanti Zebua; Abdul Munir; Irna Minauli (INSPIRA: Indonesian Journal of Psychological Research, 2021)
Changing lifestyle or habits means changing one’s perspective and changing their paradigm. The arrangement of good behavior through the provision of healthy lifestyle modules to patients undergoing hemodialysis therapy should be supported with high motivation. The study aims to find out the effect of providing healthy lifestyle modules and motivation to improve the quality of life of patients. This study is an experimental quasi-research with a 2x2 factorial design involving a sample of 30 chronic kidney disease patients undergoing hemodialysis therapy at Rumah Sakit Khusus Ginjal Rasyida Medan, North Sumatra Indonesia. Through the analysis of multiple linear regression analysis, the results showed a significant influence between the provision of healthy lifestyle modules on improving quality of life. Other findings suggest differences in quality of life between patients with high motivation levels and low-motivated patients. This study proposes further studies to examine the effectiveness of modules and improve quality of life against different patient cultural backgrounds.